Remote sensing of leaf responses to leaking underground natural gas - Smith, Karon Lesley (2002)
Detection of leaking gas pipelines is important for safety, economic and environmental reasons. Remote sensing of vegetation offers the potential to identify gas leakage. The research aim was to determine the effects of elevated soil concentrations of natural gas on overlying vegetation. Pot-scale investigations were carried out to determine whether changes in spectral characteristics were specific to natural gas or were a generic response to soil-oxygen displacement. Natural gas, argon, nitrogen and waterlogging were used to displace soil-oxygen. Leaf response to soil oxygen displacement was increased reflectance in the visible wavelengths and changes in the position and shape of the red-edge, which shifted towards longer wavelengths as the control plant matured, while the red-edge of the treated plant remained stationary indicating an inhibition of maturing. The shape of the red-edge differed in bean and barley with bean exhibiting a single peak in the first derivative that moved with plant maturity; barley exhibited a peak at 704 nm with a shoulder at 722 nm that shifted to shorter wavelengths during plant stress. Argon and waterlogging exhibited a greater response than natural gas, which had been administered noncontinuously. These experiments suggest the response to natural gas was generic to soil-oxygen deficiency. Field studies were conducted to determine whether spectral changes in leaves identified in pot trials were observable in crop canopies under field conditions. Reflectance of barley growing above a leaking gas pipeline was increased in the visible wavelengths and the red-edge was at a shorter wavelength. When the majority of the crop was fully developed, the barley above the gas leak was greener, suggesting that development was inhibited by soil-oxygen displacement. It might be possible to detect leaking gas by remote sensing of vegetation in conjunction with pipeline maps, but limitations in the spatial resolution of current satellite sensors and the infrequency of cloud free skies in the UK suggest that further work is needed before an operational system could be available.